Temperature-size responses alter food chain persistence across environmental gradients - Sentis, Arnaud; Binzer, Amrei; Boukal, David S (Ecology letters, 2017)
Body-size reduction is a ubiquitous response to global warming alongside changes in species phenology and distributions. However, ecological consequences of temperature-size (TS) responses for community persistence under environmental change remain largely unexplored. Here, we investigated the interactive effects of warming, enrichment, community size structure and TS responses on a three-species food chain using a temperature-dependent model with empirical parameterisation. We found that TS responses often increase community persistence, mainly by modifying consumer-resource size ratios and thereby altering interaction strengths and energetic efficiencies. However, the sign and magnitude of these effects vary with warming and enrichment levels, TS responses of constituent species, and community size structure. We predict that the consequences of TS responses are stronger in aquatic than in terrestrial ecosystems, especially when species show different TS responses. We conclude that considering the links between phenotypic plasticity, environmental drivers and species interactions is crucial to better predict global change impacts on ecosystem diversity and stability.
Keywords: Temperature; Food Chain; Ecosystem; teplota; paradox of enrichment; Body size; Global Warming; velikost těla; klimatické změny; climate change; Climate Change; Body Size; temperature-size rule; interaction strength; food web; globální oteplování; phenotypic plasticity; potravní řetězec; ekosystém